On lattice oscillator equilibrium equation with positive infinite-range many-body potentials - Skrypnik, W.I. (Condensed Matter Physics, 2010)
The symmetrized lattice Kirkwood-Salsburg (KS) equation for the Gibbs grand canonical correlation functions of the lattice oscillators, interacting via positive infinite-range manybody potentials, is solved. The symmetrization is based on the superstability condition for the potentials.